State of the Problem of Media Literacy Management for Young People to Prevent Social Violence in the Social Media - Sujittavanich, Marisa; Sinthusakun, Pongsai (Journal of Management Science Nakhon Pathom Rajabhat University, 2024)
The purpose of this research was to study the statement of the problem in media literacy management for young people to prevent social violence on social media. The quantitative methods The population used in this study is 20,913 students of the Nakhon Pathom Provincial Secondary Educational Service Area Office, 29 schools. The sample group consisted of 358 lower secondary school students in Nakhon Pathom province using a multi-stage random sampling method. The research tools used were questionnaires, statistics used in data analysis such as percentages, averages, and standard deviations. The research results found that The problem of managing media literacy for youth to prevent social violence on social media. Overall, it is at a high level as follows: Problems of social violence on social media include: 1. Access to social media Saw news with violent content on commercial social media. 2. Social media analysis Able to use previous knowledge and experience to consider information. 3. Social media evaluation Able to distinguish which types of social media are of quality, usefulness and can be shared with others/friends. 4. Social media synthesis Able to determine which information from social media is reliable or not. 5. Social media creation You can create your own social media and 6. The problem of managing media literacy for youth Overall, it is at a high level as follows: There should be media literacy skills to prevent social violence problems on social media. Suggestions: There should be a learning plan for media literacy management problems for youth to prevent social violence problems. on social media Article history: Received 12 July 2023 Revised 11 November 2023 Accepted 15 November 2023 SIMILARITY INDEX = 5.65 %